Prediction of non‐biochemical recurrence rate after radical prostatectomy in a Japanese cohort: Development of a postoperative nomogram. (8th November 2013) - Okubo, Hidenori; Ohori, Makoto; Ohno, Yoshio; Nakashima, Jun; Inoue, Rie; Nagao, Toshitaka; Tachibana, Masaaki
<x xml:space="preserve">Abstract</x> Objective To develop a nomogram based on postoperative factors and prostate‐specific antigen levels to predict the non‐biochemical recurrence rate after radical prostatectomy in a Japanese cohort. Methods A total of 606 Japanese patients with T1‐3N0M0 prostate cancer who underwent radical prostatectomy and pelvic lymph node dissection at Tokyo Medical University hospital from 2000 to 2010 were studied. A nomogram was constructed based on Cox hazard regression analysis evaluating the prognostic significance of serum prostate‐specific antigen and pathological factors in the radical prostatectomy specimens. The discriminating ability of the nomogram was assessed by the concordance index (C‐index), and the predicted and actual outcomes were compared with a bootstrapped calibration plot. Results With a mean follow up of 60.0 months, a total of 187 patients (30.9%) experienced biochemical recurrence, with a 5‐year non‐biochemical recurrence rate of 72.3%. Based on a Cox hazard regression model, a nomogram was constructed to predict non‐biochemical recurrence using serum prostate‐specific antigen level and pathological features in radical prostatectomy specimens. The concordance index was 0.77, and the calibration plots appeared to be accurate. Conclusions The postoperative nomogram described here can provide valuable information regarding the need for adjuvant/salvage radiation or hormonal therapy in patients after radical prostatectomy.